A escolarização de crianças com transtorno do espectro autista: uma possibilidade de emancipação - Santos, Régia Vidal dos (2016)
This dissertation has as subject of study the emancipatory perspective of children’s schooling process with Autism Spectrum Disorders (ASD), and has as object the analysis of this perspective in the process of education of children with ASD enrolled in the initial years of two elementary schools of São Paulo educational system. The research was guided by the following questions: does the political-pedagogical routing of the management and teaching staff for children with ASD, translate into an emancipatory perspective? How is the educational work with children with ASD in two public schools of São Paulo school system developed? How do the agents involved in this process receive and forward this issue? It was considered the hypothesis that there is a recognition in the school community that, from a legal point of view, the inclusion of children with ASD is an assignment of the school, but, given the pedagogical, cultural and structural conditions in which it is immersed, this inclusion does not materialize in an emancipatory educational project. The theoretical reference that supported this work was the emancipatory education concept of Paulo Freire. Based on the assumptions of qualitative methodology of empirical and theoretical character, case studies were carried out from data collected though semi-structured interviews with the children with ASD, family, managers, teachers and staff at two schools of the municipality of São Paulo, with a responsible technician of the Center of Pedagogical Support Specialized (CAPE); and with a public prosecutor of Group of Special Education Actuation of the Public Ministry of State of São Paulo (GEDUC); and through a focal group with classmates of children with ASD. In the course of research and in their final considerations, we realize that there is legal recognition that the inclusion of children with ASD is a school assignment, but the emancipatory perspective, in neither of the two schools is hegemonic. In one of them that liberating approach is announced, when we look at the efforts of educators who, by betting on the dimension of “being more” of his student, seek to recreate the practice itself from the reading of the pedagogical reality, which suggests ways to build an emancipatory perspective in the educational process of children with Autism Spectrum Disorder.